Keanekaragaman Serangga pada Bunga Tomat (Lycopersicon esculentum Mill.) di Lahan Pertanian Organik - Mosi Retnani Fajarwati; Tri Atmowidi; Dorly Dorly (Jurnal Entomologi Indonesia, 2009)
Study on the diversity of insect visitors on tomato flowers were conducted at Bina Sarana Bakti (BSB) organic farm, Cisarua, West Java. Diversity of insects were observed by observational method, an 10 m2 area of tomato plants in the morning, mid-day, and afternoon. Observations were conducted during 20 days. Diversity of visiting insects were analyzed by Shannon diversity and its evenness. Similarity of visiting insects between time of observations were analyzed by Jaccard similarity index. In organic farm, insect visitors of tomato plants consist of six orders belonging to eight species. Insect visitors of tomato flowers were dominated by Thrips sp. (Thysanoptera) and Hylaeus sp. (Hymenoptera). Hylaeus sp. was a main pollinator of tomato plants. Diversity of insect visitors in the morning and mid-day was higher than in the afternoon. Evenness of insect visitors of tomato flowers between observation times were relatively equal.